Associations between motorized transport access, out-of-home activities, and life-space mobility in older adults in Japan - Yen Tran; Naohisa Hashimoto; Takafumi Ando; Toshihisa Sato; Naoki Konishi; Yuji Takeda; Motoyuki Akamatsu (BMC, 2022)
Abstract Background Motorized transport access and out-of-home activities are two potential correlates of Life-space mobility (LSM), a common research topic in mobility studies of older adults. These correlates remain mostly unexplored in previous literature and relating them with LSM can reveal directions for improving the LSM of older adults. Methods The associations between motorized transport access, out-of-home activities, and LSM were examined using data from 1,333 older adults (mean age = 70.63) living in 15 cities and towns in Japan. LSM was assessed using composite life-space assessment (LSA) scores. Motorized transport access was measured using dummies showing whether a person had car access (divided into five levels) and used public transport (bus and railway), and out-of-home activities were measured using the number of various activities that were conducted during the most recent weekday and weekend day. Generalized linear models were used to assess the associations. Results The sample was dominated by males (74.42%), with more than half of the sample had their own cars. On average, each respondent had four activities during two survey days, and shopping was the most common activity. The results showed that owning a car and using railway, as well as various activities were associated with increased composite LSA scores, whereas no cars or only shared cars in home were associated with decreased composite LSA scores. However, these associations differed between males and females. Conclusions In this study, different levels of motorized transport access and different types of out-of-home activities were found to associate differently with composite LSA scores. Based on these findings, we suggest that policymakers should provide more transport access, pay more attention to the LSM of older adults with high clinics/hospital activities, and trigger more shopping and daily leisure activities for older adults to improve the LSM of this population.